2020
DOI: 10.1038/s41598-020-66404-z
|View full text |Cite
|
Sign up to set email alerts
|

Does entry to center-based childcare affect gut microbial colonization in young infants?

Abstract: Entry to center-based childcare (CC) at three months of life can be an important challenge for infants as it includes major stressors such as long maternal separations and frequently changing caregivers. Stress and the new environment may in turn alter the composition of the gut microbiota with possible implications for future health outcomes. As part of an ongoing longitudinal study, we investigated whether CC, as compared to being cared for by the parents at home, alters the composition of the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 64 publications
(69 reference statements)
1
21
0
1
Order By: Relevance
“…Source : The redundancy analysis representation was taken from Hermes et al. (2020), the non‐metric multidimensional scaling was taken from Adams et al. (2017), the bar graph of the linear discriminant analysis effect size was taken from Hoffman et al.…”
Section: Advanced Data Analysis and Visualisationmentioning
confidence: 99%
“…Source : The redundancy analysis representation was taken from Hermes et al. (2020), the non‐metric multidimensional scaling was taken from Adams et al. (2017), the bar graph of the linear discriminant analysis effect size was taken from Hoffman et al.…”
Section: Advanced Data Analysis and Visualisationmentioning
confidence: 99%
“…Early education and child care programs across the country have reported substantial drops in enrollment attributable to statewide or voluntary center closures throughout the pandemic along with parental preferences not to enroll in daycare in order to limit COVID-19 exposures. 31 While longitudinal studies have suggested that entry into childcare versus continued care at home by parents does not impact an infant's microbial composition, research in this area is nascent and data from existing studies reflect pre-COVID-19 behaviors. 32 Restricted travel either due to state mandates or personal preferences have also occurred over the last 12 months, with a 43% reduction in air travel compared with 2019.…”
Section: Daycare and Travel Exposurementioning
confidence: 99%
“…The gut microbiota plays a critical role in many fundamental aspects of health, and its normal development at early ages is required to maintain host fitness during childhood and later in life [1,2]. Longitudinal studies have uncovered that the gut microbiota develops in a relatively dynamic pattern in infancy and toddlerhood [3][4][5]. Importantly, this ecological succession may not come to an end within the first 3 years of life as previously believed [6,7], but changes continue at least until middle childhood, likely as a result of external influential factors [8].…”
Section: Introductionmentioning
confidence: 99%